2020
DOI: 10.1038/s41598-020-64716-8
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the taphonomic signature of wolves from humans and other predators on small prey assemblages

Abstract: However, despite being one of the most ubiquitous carnivores in prehistoric archaeological sites, the role of the wolf (Canis lupus) as an agent responsible for accumulations of small-prey remains has never been examined. Wolves are a widespread Holarctic species distributed across a broad variety of habitats, including deserts, dry plains, boreal forests, and the High Arctic 28. They are generalist carnivores, feeding on a wide variety of species throughout their range. Wild ungulates (e.g. red deer, roe deer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 44 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…One must consider the possibility that other carnivores, such as canids, could have had access to the remains. Wolfs, for example, are known to completely consume rabbit remains, thus this would result in a large, digested sample (Lloveras et al 2020) but this is not found in the assemblage, and the implementation of sieving certainly diminished recovery bias. The importance of dogs in Late Prehistory contexts is noteworthy, since they probably ate human-abandoned waste, resulting in a different patterning of body parts, besides distinguishable tooth marks and digestion degrees, but data is lacking for better comparison (Almeida et al 2022).…”
Section: Tab 7 Different Taphonomical Indicators' Absolute and Relati...mentioning
confidence: 99%
“…One must consider the possibility that other carnivores, such as canids, could have had access to the remains. Wolfs, for example, are known to completely consume rabbit remains, thus this would result in a large, digested sample (Lloveras et al 2020) but this is not found in the assemblage, and the implementation of sieving certainly diminished recovery bias. The importance of dogs in Late Prehistory contexts is noteworthy, since they probably ate human-abandoned waste, resulting in a different patterning of body parts, besides distinguishable tooth marks and digestion degrees, but data is lacking for better comparison (Almeida et al 2022).…”
Section: Tab 7 Different Taphonomical Indicators' Absolute and Relati...mentioning
confidence: 99%